Optimasi Ekstraksi Minyak Kulit Biji Mete Dengan Metode Microwave Assisted Extraction (MAE) - Cristiany Gunu Lengari; Stevanie Aurelia Lifindra; Martinus Edy Sianto; Suratno Lourentius (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2022)
In the processing of cashew nuts (Anacardium Occidentale L.) cashew seeds will be produced and the by-product is cashew nut shell. Cashew nut shells contain oil or cashew nut shell liquid (CNSL). Cashew nut shell oil is used in the pharmaceutical industry as an anti-cancer agent and also in the industrial sector as a raw material for car brake oil. The purpose of this study was to study the optimum conditions for extracting cashew nut shell oil using microwave assisted extraction (MAE). Optimization is determined by the Response Surface Methodology (RSM) method to see the relationship between the influential variables, namely temperature (50, 63, 75oC) and time (2, 6, 10 minutes). Anarchic acid contained in cashew seed oil at optimum conditions was analyzed using Gas Chromatography – Mass Spectroscopy (GC – MS). From the optimization of the yield of cashew seed shell oil extraction, it was found that the optimum conditions were at extraction time of 31.7 minutes and temperature of 68.50C with cashew seed oil yield of 41.27%. Analysis of cashew seed oil at optimum yield using GC-MS found that the anarchic acid content was 30.11%.